2020
DOI: 10.33021/firm.v5i1.793
|View full text |Cite
|
Sign up to set email alerts
|

Who Is The Target Market Of Digital Tourism 4.0?

Abstract: <p>This study is to investigate the willingness or intention of millennials and Gen Z era because nowadays, they are the new target market and their tourism destination image to visit several places in Indonesia based YouTube account "Indonesia.Travel" about their promotional video "Wonderful Indonesia-A Visual Journey." In this video, there will be four places. The first one is Bunaken, Manado; Banyuwangi, East Java; Lombok; and Wakatobi. The paper is presenting and experimental research (pre-test and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The younger generation utilizes cheap promotions amid crises to purchase tourism products (Chew & Jahari, 2014). This finding supports Goenadhi & Rahadi (2020), which found that Millennials and Gen Z tourists have the desire to travel but lack enough money. Therefore, they take advantage of the discount offered during the pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…The younger generation utilizes cheap promotions amid crises to purchase tourism products (Chew & Jahari, 2014). This finding supports Goenadhi & Rahadi (2020), which found that Millennials and Gen Z tourists have the desire to travel but lack enough money. Therefore, they take advantage of the discount offered during the pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…The most updated research underlines the value of some intrinsic features that could affect purchasing travel habits. These features are authenticity (Haddouche and Salomone, 2018), nostalgia or inclusiveness (Ruspini, 2019), as well as sustainability and digitalisation as mentioned above (Monaco, 2018; Goenadhi and Rahadi, 2020; Çalişkan, 2021; Mavragani and Dionysios, 2022; Buhalis and Karatay, 2022). Special attention is also paid to the relevance of food as an attractive element for the generation under investigation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of tourism infrastructure, such as improved roads, transportation systems, and tourist information centres, has made it easier for tourists to navigate and explore the region. Banyuwangi's hospitality industry has been proactive in providing quality services and ensuring visitor satisfaction, contributing to positive word-of-mouth and repeat visits (Goenadhi & Rahadi, 2020). Collaboration and partnerships have played a vital role in Banyuwangi's tourism market orientation.…”
Section: Banyuwangi Tourism's Market Orientationmentioning
confidence: 99%